Penerapan Logika Fuzzy untuk Kendali Suhu Ruangan dengan Air Conditioner pada Rumah dan Kantor - Adrianus Raffel; Yoga Alif Kurnia Utama (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2023)
The purpose of this research is to build a fuzzy logic system using the mamdani method which can control room temperature with Air Conditioner (AC) in homes and offices so that every room in the house and office that uses Air Conditioner (AC) as air conditioner gets optimal temperature so it doesn't affect the health of people in the room, saves electricity usage, and can extend the life of the Air Conditioner (AC) itself. In this study several parameters will be used such as room size, number of Air Conditioners (AC) in one room, Air Conditioner (AC) specifications, and the number of people in one room where these parameters will be taken from daily life in Indonesia. Then from these parameters will be processed with fuzzy logic using the mamdani method so that it will produce an output in the form of what is the optimal temperature that will be issued by the Air Conditioner (AC) in the room.